Tough as they come - Mills, Travis; Brotherton, Marcus (New York : Convergent Books, 2015)
"During his three combat-filled tours of duty in Afghanistan, former college sports star and skilled paratrooper U.S. Army Staff Sergeant Travis Mills never once backed down from the hardest challenges that came his way. The big, likable guy literally woke up every morning proudly singing the 82nd Airborne song to encourage and motivate the men he led. But late one afternoon in April 2012 while Travis and his men were on a routine mission near a remote village in southern Afghanistan, the unthinkable happened. While patrolling for improvised explosive devices (IEDs), the minesweeper missed one IED, and Travis Mills's world changed forever. In this vivid account of Travis's heroic fight for survival, he recalls the action-packed and challenging days of his earlier tours of duty with the legendary 82nd Airborne Division, the agony of encountering a hidden bomb while on patrol with his men, and his odds-defying physical and spiritual struggle afterward to come back from severe quadruple amputee injuries and rebuild his life. This searing and unforgettable true story will inspire, encourage, challenge, and motivate you forward. It shows how resilient the human spirit is, how unbreakable the will is when pressed with difficult demands, and how triumphant a person can be when tasked with the seemingly impossible. "Every day is a challenge," Travis says, "but every challenge can be overcome. I'm not wounded anymore. If you're wounded, then you're still focused on your injury. I'm just a man with scars living life to the fullest and best I know how.""--
Keywords: Mills, Travis; United States. -- Army. -- Airborne Division, 82nd.; Afghan War, 2001- -- Personal narratives, American; Disabled veterans -- United States -- Biography; Amputees -- United States -- Biography; Soldiers -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Military; RELIGION / Christian Life / Inspirational